Uso de la Somatotropina bovina recombinante, en vacas primerizas y multiparas de raza holstein friesian y su efecto en la producción de leche - Tarrillo Blas, Christian Samuel (2011)
This study was realized by the purpose of evaluating the effect of recombinant bovine somatotropin (rBST, in primiparous and multiparous of race Holstein Friesian on the production of milk. There used 80 cows of the race Holstein Friesian (primiparous and multiparous) of different days of lactation, distributed in a design in blocks completely at random, with two treatments. The treatments were: Control (T0) and experimental (T1). It was applied from the 110th by STBr's applications every two weeks for 11 weeks. For the statistical analysis there was in use the analysis of variance and Duncan's test. The results for production of milk were To = 22,32 Lts. and T1 = 26,16 Lts. existing significant difference between treatments (p <0,05), more not this way between primiparous and multiparous. Since complementary part also other variables were evaluated as: The corporal condition I do not present significant difference (T0 = 2,91 and T1 = 3,00) between treatments (p> 0,05) but, if there was significant difference (p <0,05) between primiparous (2,85) and multiparous (3,06). In the evaluation of solid total there was no significant difference between treatments (p>0,05), but if between primiparous and multiparous (9,11 vs 9,93) respectively. Another evaluated variable was the sanitary condition of the mammary gland (mastitis clinic and subclinic), not being significant differences (p> 0,05) for primiparous and multiparous. The results allow to conclude that the recombinant bovine somatotropin increases the production of milk in the primiparous cows and multiparous and it did not show negative effect on the total solids ones, corporal condition and health of the mammary gland.